Penerapan Metode Tutor Sebaya untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika Materi FPB dan KPK pada Siswa Kelas IV SDN 1 Langkapura - Mardiana Mardiana (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
This type of research is classroom action research. The subjects of this study were 40 grade students of SDN 1 Langkapura for the 2018/2019 academic year, with a total of 40 students consisting of 21 male students and 19 female students. Data collection techniques used test and non-test techniques. The results showed that students' completeness in classical learning increased from 57.5% in the pre-cycle to 70% in the first cycle and increased again to 85% in the second cycle. The data has reached the set success indicator, which is 85%. The average score of the students' formative tests increased from 58.0 in the pre-cycle stage to 69.75 in the first cycle and to 76.50 in the second cycle. These data have reached an indicator of research success, namely the average score of students ≥ 60. The number of students who scored above the KKM has also increased. In the pre-cycle stage there were 23 students or 57.5%, increasing in the first cycle to 28 students or 70% and again experiencing an increase in the second cycle to 34 students or 85%. This data has reached an indicator of research success, namely the number of students who score above the KKM by 75%.